Vehicle and reliable driver scheduling for public bus transportation systems. (March 2021) - Andrade-Michel, Alejandro; Ríos-Solís, Yasmín A.; Boyer, Vincent
Highlights: We study the integrated bus vehicle and reliable driver scheduling problem. Driver's reliability is the key concept that improves the operational assignments. We reduce the number of no-covered to improve the user's satisfaction. A constraint programming model is compared with a variable neighborhood search. Enormous gains obtained in covered trips when the drivers' reliability is considered. Abstract: We propose the bus vehicle and reliable driver scheduling problem that is an integrated approach for the vehicle and the crew scheduling problems considering driver's reliability information to reduce the number of no-covered trips along the day and thus improve the user's satisfaction. An exact constraint programming model is proposed and compared with a variable neighborhood search that incorporates the driver's reliability and the trip's importance. The obtained trip-vehicle-driver assignments are evaluated on many scenarios with a Monte Carlo method to simulate the driver's absenteeism. Experimental results on randomly generated instances based on a real case study show our methodologies' efficiency and the enormous gains in covered trips when the drivers' reliability is considered.